Architectural And Structural System Design of Precast Concrete Structures In Earthquake Zones - dağ, ilknur; Kuruşcu, Ali Osman; Parsa, Ali Rıza (Publisher Cv. Inara, 2022)
Precast concrete systems, which are the result of industrialization in the field of construction, are faced with the prejudice of insufficient earthquake resistance despite their many advantages and their use is limited in Turkey. These systems, which have proven earthquake resistance if they are designed properly, can be used safely in low-rise or multi-storey buildings with different functions in earthquake zones. The aim of this study is to determine the architectural design requirements of earthquake-resistant precast concrete structures and to reveal the structural system design approaches. In accordance with this aim, the earthquake effect on the structures was summarized and architectural design principles that would contribute to the earthquake resistance of precast concrete structures were determined firstly. Then, earthquake-resistant structural system design approaches of frame, panel, and cell construction were evaluated separately.